Case Report: Psychoacoustic Analysis of a Clarinet Performance With a Custom-Made Soft Lip Shield Worn to Prevent Mucosal Erosion of Lower Lip - Tanabe, Gen; Hattori, Mariko; Obata, Satoshi; Takahashi, Yuumi; Churei, Hiroshi; Nishiyama, Akira; Ueno, Toshiaki; Sumita, Yuka I. (Frontiers in Psychology, 2022)
Abstract Introduction: Wind instrument players sometimes suffer from erosion of the mucous membrane of the lip. This is caused by the action and pressure of the mouthpiece of the wind instrument against teeth. To address this problem, a lip shield is fitted over the dental arch to prevent direct contact between the lips and teeth. However, there are a few studies on the influence of the lip shield on the acoustics of wind instruments. The purpose of this study was to analyze the psychoacoustics of a clarinet performance with the player wearing a custom-made soft lip shield to prevent mucosal erosion of the lower lip. Case description: A lip shield was custom-made with a soft thermoplastic material for a female clarinetist who complained of mucosal erosion and pain of the lower lip. The psychoacoustics of her musical performance played in different dynamics, fortissimo, mezzo forte and pianissimo were analyzed, including loudness and sharpness. A self-evaluation questionnaire with items rated on a 10-point scale was administered. After wearing the lip shield, the patient reported that the mucosal erosion and pain of her lower lip when playing clarinet resolved. The lip shield had little effect on the loudness. There was a slight decrease in sharpness when the lip shield was worn compared to when it was not, describing the reduction of high frequencies. Furthermore, fewer variations in sharpness between the tones were observed. Conclusion: The results suggest that lip shields made of soft materials can eliminate mucosal erosion and pain of the lower lip while having little effect on performance, although, a slight change in timbre is possible.